2022
DOI: 10.1186/s42779-022-00159-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of tauco as Indonesian fermented soybean paste

Abstract: Tauco is a fermented soybean paste like miso but typical from Indonesia, commonly used as umami seasoning. This study objective was to evaluate the nutritional composition of diverse tauco products found in Indonesia and to determine a potential tauco product characterized by certain amino acids related to umami peptides (Asp, Glu, Gly, Ser, Thr, Val). Proximate composition, NaCl salt, total sugars, total acids, and total amino acid profiles of 24 tauco products, collected from 24 producers in 7 provinces in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Tauco is a fermented soybean product from Indonesia, rich in protein and amino acids (Herlina et al ., 2022). It has a distinctive culinary flavour for many Indonesian dishes (Lestari & Aprillia, 2021), including its umami taste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tauco is a fermented soybean product from Indonesia, rich in protein and amino acids (Herlina et al ., 2022). It has a distinctive culinary flavour for many Indonesian dishes (Lestari & Aprillia, 2021), including its umami taste.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the salt fermentation of food protein sources results in an umami taste, which is found in tauco. A previous study showed that free amino acids played an essential role in the taste of tauco (Herlina et al ., 2022). However, umami peptides could also contribute to the taste of tauco because the presence of peptides was relatively abundant, and the intensity of the umami taste cannot be explained by the concentration of only free umami amino acids (glutamic acid concentration).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, soybeans are often consumed in processed forms such as tofu, tempeh, soy sauce, soy milk, etc. [3,4]. Soybean is a plant with a taproot system, two types of stem growth (determinate and indeterminate), and a trifoliate leaf.…”
Section: Introductionmentioning
confidence: 99%